Implementation Of Path Goal Theory In Organizational Communication And Leadership Research - Asih Handayanti; Tamy Ali Januarty (SEAN Institute, 2023)
The ability to create teamwork is determined by one's leadership competence. The application of leadership must be conditionally adjusted to circumstances or conditions that frequently change. Leadership also speaks about the behaviour of the leader in question. Regarding leader behaviour and leadership can be seen through the path goal theory of leadership. The aim of this research is to discuss Path-Goal Theory in communication studies or research, especially in studies of organizational communication and leadership. This theory is considered a path-goal theory because it focuses on how leaders influence followers' perceptions of work goals, self-development goals, and the paths needed to achieve goals. The path goal leadership model states the importance of the leader's influence on subordinates' perceptions of work goals, self-development goals, and paths to goal achievement.